2022
DOI: 10.1007/s11356-021-18458-3
|View full text |Cite
|
Sign up to set email alerts
|

Source apportionment, ecological, and human health risks of toxic metals in road dust of densely populated capital and connected major highway of Bangladesh

Abstract: This study investigates pollution levels, source apportionment, ecological and human health risks associated with toxic metals (Pb, As, Hg, Cr, and Cd) in road dust from the most populated Dhaka city and a connected major highway in Bangladesh. The mean concentration of Pb, Hg, and Cd were 1.3, 29.3, and 13.2 times higher than their corresponding background values with spatially uneven distribution all over the study area. Metal pollution indices, the geoaccumulation index (I geo ), NIPI, PI, indicated extrem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…The study revealed severe pollution in many sampling sites, primarily attributed to local environmental factors. 29 These studies provide additional evidence of the impact of human activities on metal pollution in various regions, highlighting the importance of pollution indices in assessing and understanding the sources and levels of pollution.…”
Section: Software Analysis Results (Arcgis)mentioning
confidence: 96%
“…The study revealed severe pollution in many sampling sites, primarily attributed to local environmental factors. 29 These studies provide additional evidence of the impact of human activities on metal pollution in various regions, highlighting the importance of pollution indices in assessing and understanding the sources and levels of pollution.…”
Section: Software Analysis Results (Arcgis)mentioning
confidence: 96%
“…Therefore, these ve extracted components were included in the widely used EPA-PMF 5.0 model to infer the NORMs' and elements' source prole contribution and provenance. 34,64,67,[100][101][102] As demonstrated in Fig. 5a, factor-1 is predominantly characterized by 61.4, 48.7, 47.5, and 41.4% of the Eu, Hf, P HREE, and Yb concentrations, respectively.…”
Section: Co-occurrence Of Radionuclides With Elementsmentioning
confidence: 91%
“…where the amount of element j of sample i is represented as x ij , the quantication of factor k to the sample i is referred to as g ik , the contribution of element j in factor k is denoted by f kj , the abundance of residues for the j element in the i sample is e ij , and the factor number is indicated by p. Non-negative factor contributions are required for an accurate interpretation of the operation. 64 For the PMF model to work, g ik and f kj must remain constant as the objective function and Q must be reached at its lowest. The Q value signies modelling quality.…”
Section: Different Environmental Pollution and Radiological Indices A...mentioning
confidence: 99%
“…Increasing demand for metals in industries and urbanization process have strongly disturbed the natural geochemical cycling of the urban ecosystem [5,6], and urbanization processes can result in the accumulation of HEs in surface dust in urban ecosystems [7,8]. Traffic exhaust, incinerators, industrial waste, and the atmospheric deposition of dust and aerosols have continuously added HEs to the urban environment [9], and HEs accumulate in the human body can cause irreversible damage to human health [10,11]. Therefore, HEs in surface dust can serve as a comprehensive indicator of the quality of the urban environment [12].…”
Section: Introductionmentioning
confidence: 99%